Future-Oriented Learning and Working (ZOLA) as a Contribution to Democratic Education: A Qualitative Study at a UNESCO Secondary School (Pedagogical Horizons, 2025)
This article examines the concept of Future-Oriented Learning and Working (ZOLA) at a UNESCO secondary school as a contribution to democratic education. ZOLA is conceived as an innovation and school development strategy that links project-based, interdisciplinary, and socially relevant learning with the Sustainable Development Goals (SDGs). Based on guided interviews with students and teachers and a qualitative content analysis, the study identifies both potentials and challenges of this format. The findings indicate that ZOLA fosters participation, self-efficacy, and social competencies among learners, while at the same time revealing tensions regarding curricular requirements, assessment practices, and organizational structures. Key conditions for success include clear processes, a formative feedback culture, and the professional role of teachers as coaches and learning facilitators. The article therefore discusses ZOLA not only as a didactic approach but also as a school development strategy that can sustainably strengthen democratic school culture and participation structures.
Keywords: school development; democratic education; participation; project-based learning; self-efficacy